PENGEMBANGAN MEDIA SMART WINDOW AND WALL PICTURES DALAM PEMAHAMAN BERITA HOAX DI SD SE-KECAMATAN MALINAU KOTA - Donna Rhamdan; Holly Bill; Arman Arman (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2019)
Abstract: The development of smart window and wall pictures media in this study was made so that students understood the hoax news. Thedevelopment of research is done in order to overcome the problemsfaced by students who have not been able to distinguish the right newsand false news (Hoax) . The research was conducted with Research andDevelopment . The media is validated by linguists and media experts,and is tried out to small groups to find out news about hoaxes, soresearchers can draw conclusions that the development of smart windowand wall pictures can be used as a medium for understanding hoax newsin the Malinau City sub-district.